ENHANCEMENT STUDY OF POLYMER RAPID TOOLING FOR METAL INJECTION MOLDING - QAYYUM, JUNAID AHMAD (2018)
Machined metal mold are used for high-volume manufacturing of metal injection molding (MIM) parts. The main limitations associated with the machined metal mold are that its manufacturing is pricy and time consuming